2022
DOI: 10.21203/rs.3.rs-2011054/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of cnidarian microbiomes reveals insights into the structure, specificity, and fidelity of marine associations.

Abstract: Microorganisms play essential roles in the health and resilience of cnidarians. Understanding the factors influencing cnidarian microbiomes requires cross study comparisons, yet the plethora of protocols used hampers dataset integration. Our objective was to unify 16S rRNA gene sequences from cnidarian microbiome studies under a single analysis pipeline. We reprocessed 12,010 cnidarian microbiome samples from 186 studies, alongside 4,002 poriferan, cultured Symbiodiniaceae, and environmental samples, unifying … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 87 publications
2
15
0
Order By: Relevance
“…By analyzing datasets from186 cnidarian and Symbiodiniaceae microbiome studies [7], we found that reads assigned to the phylum Chlamydiota are widespread in these host taxa, being detected in 1,925 individual samples out of 10,255, although usually at a low relative abundance (< 2% for all families except Psammocoridae, Figure 1). The highest relative abundance was in the scleractinian family, Psammocoridae (32% chlamydiae), although this data came from only one study (seven samples).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…By analyzing datasets from186 cnidarian and Symbiodiniaceae microbiome studies [7], we found that reads assigned to the phylum Chlamydiota are widespread in these host taxa, being detected in 1,925 individual samples out of 10,255, although usually at a low relative abundance (< 2% for all families except Psammocoridae, Figure 1). The highest relative abundance was in the scleractinian family, Psammocoridae (32% chlamydiae), although this data came from only one study (seven samples).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we analyzed previously published data from cnidarian and Symbiodiniaceae microbiome studies and eight chlamydial MAGs sequenced from cnidarian hosts (corals), to increase our understanding of both chlamydial and cnidarian biology, and lay the foundations for further studies on cnidarian-chlamydiae interactions. The sequences derived from 186 cnidarian and Symbiodiniaceae microbiome studies [7] enabled a comprehensive overview of the presence, prevalence, and diversity of chlamydiae in cnidarian holobionts. Cnidarian-associated chlamydiae were highly diverse; with the exception of members of the chordate-infecting Piscichlamydiaceae, Parilichlamydiaceae, and Chlamydiaceae, members of all other chlamydial families occur in cnidarian microbiomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations